2017
DOI: 10.1371/journal.pone.0173373
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates the chemical and microbial induction of inflammation and insulin resistance in human placenta, adipose tissue and skeletal muscle

Abstract: Gestational diabetes mellitus (GDM), which complicates up to 20% of all pregnancies, is associated with low-grade maternal inflammation and peripheral insulin resistance. Sterile inflammation and infection are key mediators of this inflammation and peripheral insulin resistance. Resveratrol, a stilbene-type phytophenol, has been implicated to exert beneficial properties including potent anti-inflammatory and antidiabetic effects in non-pregnant humans and experimental animal models of GDM. However, studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 70 publications
0
45
0
1
Order By: Relevance
“…A key strength of this study is the combined use of in vitro and in vivo models to investigate the ability of naringenin to disrupt pathways known to GDM pathophysiology. In vitro, TNF was used to recapitulate inflammation and impaired skeletal muscle glucose uptake associated with GDM pregnancies . It was found that naringenin treatment significantly improved insulin‐stimulated glucose uptake in human skeletal muscle compared to TNF treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A key strength of this study is the combined use of in vitro and in vivo models to investigate the ability of naringenin to disrupt pathways known to GDM pathophysiology. In vitro, TNF was used to recapitulate inflammation and impaired skeletal muscle glucose uptake associated with GDM pregnancies . It was found that naringenin treatment significantly improved insulin‐stimulated glucose uptake in human skeletal muscle compared to TNF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is a central feature of GDM. There is extensive evidence to suggest that low‐grade maternal inflammation contributes to the peripheral insulin resistance characteristic of GDM . Several studies have demonstrated that pro‐inflammatory mediators, such as TNF, and pathogenic factors, such as bacterial and viral products, can induce defects within the insulin signaling pathway in skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations